1994
DOI: 10.1002/etc.5620130807
|View full text |Cite
|
Sign up to set email alerts
|

Sampling the hudson river estuary for pcbs using multiplate artificial substrate samplers and congener‐specific gas chromatography in 1991

Abstract: During the summer of 1991, multiplate artificial substrate samplers were deployed at five locations in the Hudson River from Troy to Poughkeepsie, New York The sedimentary material that collected on these plates was fractionated and analyzed using a congener specific method for PCB content The results were compared intrasite, intersite, and across time We found no difference between the PCB congener distribution patterns in the coarse and fine fractions, as determined by linear regression We also found little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The Porquerolles sediment presents this change for higher chlorinated compounds (hepta-to decachlorobiphenyls) while no trends observed for lightly chlorinated compounds (from tri-to hexachlorobiphenyls). The same feature was observed by Bush et al (42), who found no difference between the PCB congener distribution patterns in the coarse (φ > 420 µm) and the fine fractions (φ < 420 µm) of sediments polluted with Aroclor 1242 mixture, lightly chlorinated industrial formulation.…”
Section: Resultssupporting
confidence: 86%
“…The Porquerolles sediment presents this change for higher chlorinated compounds (hepta-to decachlorobiphenyls) while no trends observed for lightly chlorinated compounds (from tri-to hexachlorobiphenyls). The same feature was observed by Bush et al (42), who found no difference between the PCB congener distribution patterns in the coarse (φ > 420 µm) and the fine fractions (φ < 420 µm) of sediments polluted with Aroclor 1242 mixture, lightly chlorinated industrial formulation.…”
Section: Resultssupporting
confidence: 86%
“…The New York-New Jersey Harbor Estuary (HE) and the Lower Hudson River Estuary have been greatly impacted by anthropogenic inputs of SOCs from the adjoining met-ropolitan area and, in the case of polychlorinated biphenyls (PCBs), from the Upper Hudson River (10). Elevated levels of PCBs have been found in the biota, sediments, and water column of the Hudson River Estuary (10)(11)(12)(13)(14)(15)(16)(17). Achman et al (14) determined that there was a positive flux of PCBs from the sediments to the overlying water in the Hudson River Estuary, leading in turn to enhanced fluxes of PCBs from the water column into the air.…”
Section: Introductionmentioning
confidence: 99%
“…From the mid 1940s to the mid 1970s, the Hudson River estuary received over 250 tonnes of PCBs, largely as a result of industrial discharges above the Troy Dam at Ft. Edward and Hudson Falls ( ). PCB inventories in sediments revealed a considerable concentration gradient down-estuary due to advection, dispersion, and dilution ( , ). However, as a consequence of the decades of PCB release in the upper estuary, the commercial striped bass fishery in the entire Hudson River was closed, and consumption advisories for recreational anglers were issued in 1976.…”
Section: Introductionmentioning
confidence: 99%